Clostridioides difficile Single Cell Swimming Strategy: A Novel Motility Pattern Regulated by Viscoelastic Properties of the Environment - Schwanbeck, Julian; Oehmig, Ines; Groß, Uwe; Zautner, Andreas E.; Bohne, Wolfgang (Frontiers in Microbiology, 2021)
Flagellar motility is important for the pathogenesis of many intestinal pathogens, allowing bacteria to move to their preferred ecological niche. Clostridioides difficile is currently the major cause for bacterial health care-associated intestinal infections in the western world. Most clinical strains produce peritrichous flagella and are motile in soft-agar. However, little knowledge exists on the C. difficile swimming behaviour and its regulation at the level of individual cells. We report here on the swimming strategy of C. difficile at the single cell level and its dependency on environmental parameters. A comprehensive analysis of motility parameter from several thousand bacteria was achieved with the aid of a recently developed bacterial tracking program. C. difficile motility was found to be strongly dependent on the matrix elasticity of the medium. Long run phases of all four motile C. difficile clades were only observed in the presence of high molecular weight molecules such as polyvinylpyrrolidone (PVP) and mucin, which suggests an adaptation of the motility apparatus to the mucin-rich intestinal environment. Increasing mucin or PVP concentrations lead to longer and straighter runs with increased travelled distance per run and fewer turnarounds that result in a higher net displacement of the bacteria. The observed C. difficile swimming pattern under these conditions is characterised by bidirectional, alternating back and forth run phases, interrupted by a short stop without an apparent reorientation or tumbling phase. This motility type was not described before for peritrichous bacteria and is more similar to some previously described polar monotrichous bacteria.